2008
DOI: 10.1128/cvi.00103-08
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Anthrax Toxin Is Influenced by Receptor Expression

Abstract: Anthrax toxin protective antigen (PA) binds to its cellular receptor, and seven subunits self-associate to form a heptameric ring that mediates the cytoplasmic entry of lethal factor or edema factor. The influence of receptor type on susceptibility to anthrax toxin components was examined using Chinese hamster ovary (CHO) cells expressing the human form of one of two PA receptors: TEM8 or CMG2. Unexpectedly, PA alone, previously believed to only mediate entry of lethal factor or edema factor, was found to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Indeed, contradictory results of this relationship between anthrax receptor expression level and cytotoxic effects have previously been reported in the literature, in various cell types. For example, Taft and Weiss (2005) showed that anthrax toxin toxicity was influenced by ANTXR expression, while other studies showed that despite detection of ANTXR1 and ANTXR2 mRNA levels, cells were resistant to the effects of LeTx (Abi-Habib et al 2005;Wu et al 2009). Presently, we are unable to explain the relationship between the toxin receptor expression levels and lethal toxin cytotoxicity in lung cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, contradictory results of this relationship between anthrax receptor expression level and cytotoxic effects have previously been reported in the literature, in various cell types. For example, Taft and Weiss (2005) showed that anthrax toxin toxicity was influenced by ANTXR expression, while other studies showed that despite detection of ANTXR1 and ANTXR2 mRNA levels, cells were resistant to the effects of LeTx (Abi-Habib et al 2005;Wu et al 2009). Presently, we are unable to explain the relationship between the toxin receptor expression levels and lethal toxin cytotoxicity in lung cells.…”
Section: Discussionmentioning
confidence: 99%
“…; Bonuccelli et al . ; Taft and Weiss ). However, the exact cellular distribution of ANTXR1 and ANTXR2 in human lung tissue has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mere binding of TEM8 or preventing TEM8 from binding its physiologic partner may be enough to decrease tumor vessel density. For strategies using anthrax toxin components, the outcome may be explained by protective antigen forming a pore in cell membranes that disrupts metabolic activity and causes cell swelling (29). In the case of therapeutic molecules that either bind TEM8 or block interaction with a physiologic partner, their effect may be explained Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Oral consumption of spores can lead to an oropharyngeal or gastrointestinal infection, which can be fatal. In contrast, respiratory exposure to spores leads directly to a fulminant systemic disease which is fatal without treatment (4,5). In respiratory anthrax in humans, the incubation time from infection until the onset of symptoms is estimated to be 1 to 7 days.…”
mentioning
confidence: 99%